SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN HOTEL DENGAN BERDASAR PADA KEBUTUHAN PENGUNJUNG - Syafrianto, Andri (JURNAL ILMIAH MATRIK, 2012)
Hotel selection is influenced by the objectives and the needs of visitors. Strategic location and comfortable atmosphere are also a consideration. Lack of information about the hotel became one of the problems for the visitors to determine the desired hotel when they come to a city. This research attempts to develop a decision support system that will help to make decision in hotel selection that involve number of parameters such as distance to the destination of visits, cost, facilities, and hotel class. As a case study in this research is the hotels selection in city area of Palembang, South Sumatra. Decision support system that developed in this research used mathematical method with Fuzzy Association to determine the score. The results, concluded that the decision support system developed can be used to assist hotel selection process. Keywords: Decision Support System, Hotel Selection, Fuzzy